The Influence of Social Media as Fashion Communication Media on The Environment: Analysis of Consumer Behavior of Sekolah Tinggi Agama Buddha Nalanda Students - Purwaningsih, Tatik; Phuah Kit Teng; Aming Suherman; Dian Putra Atmaja (International Journal of Environmental Communication (ENVICOMM), 2023)
The Indonesian fashion industry is very vulnerable to the fast fashion problem because it follows endless trends. Despite increasing awareness of environmental impacts, the rise of fast fashion, characterized by cheap production, high consumption, and short clothing lifespans, has led to an increase in the amount of clothing thrown away. Rapidly changing trends and excessive consumption have significant environmental impacts. In the fast fashion industry, the concept of ready-to-wear emerged because trends changed so quickly. Through social media platforms, they can see various latest clothing styles, well-known clothing brands, and popular clothing ideas. Apart from the influence of social media, they can also easily get it from e-commerce. Social media such as TikTok and Instagram are often places where fashion trends spread. Many people easily observe the fashion trends that many people wear, so they feel they have to follow the latest trends to be considered modern. As a result, they are willing to spend money to look fashionable. The fast fashion phenomenon itself causes clothing production levels to become very high and models change every season. Every time fashion trends change, all stores and consumers in the fashion industry also change their fashion collections, resulting in textile waste and damaging the environment. One of the textile wastes produced by the fashion industry is polyester. This shows that dependence on polyester makes the fashion industry one of the highest polluters in the world, due to emissions from production processes and non- biodegradable waste. This research focuses on how the influence of social media as communication media about fast fashion helps students understand fast fashion on the environment. This research method uses quantitative research methods. A total of 100 respondents used data collection techniques using a questionnaire survey by distributing questionnaires to be filled out by Sekolah Tinggi Agama Buddha Nalanda students. The results of this research show that exposure to social media influence a person's clothing style and fast fashion trends can harm the environment.